Report of the Oversight Committee on Reservations in Higher Educational Institutions Volume-II - Planning Commission (Planning Commission, 2006)
Consequent to the notification of the Constitution (Ninety-Third Amendment) Act, 2005, effecting the 104th Amendment to the Constitution in January this year, the Government of India indicated its intention to provide reservation for students coming from the socially and educationally backward classes of citizens, popularly known as 'Other Backward Classes (OBCs) in higher educational institutions.
Government of India Planning Commission
Government of India Planning Commission